2006
DOI: 10.1074/mcp.m500243-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Serological Response to Candida Cell Wall Immunome into Novel Diagnostic, Prognostic, and Therapeutic Candidates for Systemic Candidiasis by Proteomic and Bioinformatic Analyses

Abstract: In an effort to bring novel diagnostic and prognostic biomarkers or even potential targets for vaccine design for systemic candidiasis (SC) into the open, a systematic proteomic approach coupled with bioinformatic analysis was used to decode the serological response to Candida wall immunome in SC patients. Serum levels of IgG antibodies against Candida wall-associated proteins (proteins secreted from protoplasts in active wall regeneration, separated by two-dimensional gel electrophoresis, and identified by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
124
2
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 92 publications
13
124
2
2
Order By: Relevance
“…In pathogenic yeasts it participates in virulence 10 and a high Bgl2p antibody titre is a marker of systemic candidiasis. 11 Here we demonstrated that Bgl2p possess amyloidogenic features. Firstly-low solubility in SDS and resistance to protease digestion are considered to be www.landesbioscience.com Prion 93…”
Section: Discussionmentioning
confidence: 91%
“…In pathogenic yeasts it participates in virulence 10 and a high Bgl2p antibody titre is a marker of systemic candidiasis. 11 Here we demonstrated that Bgl2p possess amyloidogenic features. Firstly-low solubility in SDS and resistance to protease digestion are considered to be www.landesbioscience.com Prion 93…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have investigated the subproteome of the cell surface (73,87,301,303,380,391; M. Martínez-Gomariz, P. Perumal, S. Mekala, C. Nombela, C. Gil, and W. L. Chaffin, unpublished data). Fractionation of this subproteome employed various extraction procedures from either intact organisms or isolated cell walls.…”
Section: What's Therementioning
confidence: 99%
“…Protoplasts were collected by centrifugation for 5 minutes at 200 g at 4°C, washed twice with 0.5 M sorbitol, and resuspended in the same buffer. Incubating protoplasts in the presence of the osmotic stabilizer sorbitol enables regeneration of the cell wall, and during regeneration, cell wall constituents are released into the supernatant (41,42). After a 2-hour incubation period (43), protoplasts were pelleted, and the supernatant was sterilized by filtration (0.22-μm filters) in the presence of protease inhibitors (Pierce).…”
Section: Figurementioning
confidence: 99%